Differences in germination capacity and seedling growth between different seed morphotypes of Afzelia africana Sm. in Benin (West Africa) - Padonou, E. A.; KASSA, Barthélémy; ASSOGBADJO, Achille.Ephrèm.; CHAKEREDZA, S.; BABATOUNDE, B.; GLÈLÈ KAKAÏ, Romain (My University, 2013)
Afzelia africana is a multi-purpose woody species threatened by a lack of natural regeneration in the wild. In the present study, differences in seed germination capacity and seedling growth between morphotypes of the seeds of A. africana Sm. were evaluated. A total of 600 seeds were collected in the Sudanian and Guinean climatic zones of Africa and their lengths, widths, thicknesses, and weights were recorded. A hierarchical classification and canonical discriminant analysis were applied to the above traits of seeds from the different climatic zones. An analysis of variance with repeated measures was applied to seed morphotypes identified by hierarchical classification to test for the effect of these morphotypes on seed germination and seedling growth. Hierarchical classification helped to identify three seed morphotypes. Canonical discriminant analysis performed on these morphotypes revealed highly significant differences. Morphotype 1 consisted of seeds from the Guinean zone, while seeds from the Sudanian zone were clustered in morphotypes 2 and 3. Morphotype 1 had the longest and heaviest seeds, while the shortest andlightest seeds were from morphotype 3. Morphotype 1 and morphotype 3 seeds showed rapid germination, while only morphotype 1 seedlings displayed rapid growth. Morphotype 1, consisting of large seeds, was superior in terms of its germination ability and seedling growth, and represents the best choice for species restoration purposes.
Keywords: Afzelia africana; Benin